Penentuan Status Mutu Air Sungai Dosay Kabupaten Jayapura Dengan Metode Indeks Pencemaran - Rumabar, Anna MF; Gaspersz, Rolling S.; Moisieri, Gabriella (Peneliti.net, 2024)
This research aims to determine the water quality status of the Dosay river in Dosay village, Jayapura district, Papua province. Water quality status aims to determine the level of water pollution. The Dosay river is a place for sand and andesite mining. People who live around the river also use the Dosay river water for washing and bathing. Mining activities and community activities can cause river water to be polluted. Therefore, through this research, the water quality status of the Dosay river has been determined. The method used to determine the water quality status of the Dosay river is Pollution Index method. Water quality measurements use several chemical, physical and biological parameters. Testing of the Dosay river water quality was carried out at the Regional Health Laboratory of Papua province. There are two locations for sampling river water, namely around community settlements exceed the quality standard limit with a value of 0.38 mg/L. In river water near the mining location, it is known that several parameters have values that exceed the quality standard limits. Some of these parameters are TSS with a value of 55 mg/L, phosphate with a value of 0.76 mg/L and copper with a value of 0.045 mh/L. From the results of laboratory tests, it is known that river water around community settlements experiences light pollution and river water around mining sites experiences moderate pollution. Determination of pollution levels using the Pollution Index Method. for location 1 the Pollution Index value is 1.76. Meanwhile, for the second location, the Pollution Index value is 2.83. With this pollution index value, the Dossay River can be said to be lightly polluted